ROLE OF AUDITOR PERFORMANCE MEDIATION IN ACCEPTANCE OF AUDITOR DYSFUNCTIONAL BEHAVIOR: ATTRIBUTION THEORY PERSPECTIVE AND ROLE THEORY - Jaya, Sandy Mahendra; Sudarma, Made; Roekhudin, Roekhudin (Universitas Brawijaya, Indonesia, 2018)
The purpose of this study is to examine and to provide empirical evidence on the influence of role conflict and organizational commitment to acceptance of auditor dysfunctional behavior mediated by the Auditor Performances. Methods of data collection using survey and obtained 83 respondents who occupy functional positions of auditors and other internal supervisory apparatus on regional inspectorate in Ex Malang Residences. Data were analyzed by using Structural Equation Model - Partial Least Square (SEM-PLS). The result of the research shows that role conflict influence to acceptance of auditor dysfunctional behavior, organizational commitment negativelyinfluence to acceptance of auditor dysfunctional behavior, role conflict negatively influence to auditor performance, organizational commitment positivelyinfluencetoAuditor Performance, Auditor Performance negativelyinfluence to acceptance of auditor dysfunctional behavior, role conflict role conflict indirectly effect on acceptance of auditor dysfunctional behavior through Auditor Performance, and organizational commitment indirectly effect on acceptance of auditor dysfunctional behavior through Auditor Performance. The results of this study can be considered to minimize dysfunctional behavior of local government internal auditors by increasing organizational commitment and performance and reduce role conflict so as to improve the quality of internal audit results.